Core microorganisms promote the transformation of DOM fractions with different molecular weights to improve the stability during composting. (March 2020) - Zhu, Longji; Wei, Zimin; Yang, Tianxue; Zhao, Xinyu; Dang, Qiuling; Chen, Xiaomeng; Wu, Junqiu; Zhao, Yue
Graphical abstract: Highlights: LMW DOM was gradually transformed into HMW DOM during composting. Core microorganisms associated with DOM transformation were identified. Chemoheterotrophy was the major function of microorganisms during composting. T, moisture and pH were key physicochemical factors affecting DOM stabilization. Abstract: Transformation of DOM fractions with different molecular weights during composting of chicken manure (CM), garden waste (GW) and municipal solid waste (MSW) was evaluated in this study. The results revealed that DOM concentrations decreased by 49.8%, 53.9% and 86.4% during CM, GW and MSW composting, respectively. Meanwhile, low molecular weight (<650 Da) DOM was visibly transformed into high molecular weight (>10 kDa) DOM for enhancing their stability during composting. Core microorganisms promoting DOM stabilization were identified by network analysis, such as Prosthecobacter, Paenalcaligenes and Solibacillus . In addition, DOM composition was also related to the relative abundance of microbial metabolic function, such as chemoheterotrophy and aerobic chemoheterotrophy. Moreover, temperature, moisture and pH were identified as the key physicochemical factors affecting the DOM stabilization mediated by core microorganisms during composting. These above findings are helpful to regulate the DOM stabilization during composting and improve the quality of final composts.